Penyelesaian Sengketa Tanah Ulayat melalui Lembaga Adat: Studi Desa Tarlawi Wawo Kabupaten Bima - Eva Putri Salsabilla; Ridwan Ridwan; Ihlas Ihlas (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This study examines the mechanisms for resolving customary land disputes through customary institutions in Tarlawi Village, Bima Regency, as well as their status within the national legal system. This is an empirical study using a case study approach, employing data collection techniques such as interviews, observation, and documentation. The results show that dispute resolution is conducted through a traditional deliberative forum involving traditional leaders (gelarang), village officials, and the disputing parties. This mechanism reflects the practice of legal pluralism as it brings together customary law, village government policies, and state law. Furthermore, this resolution model aligns with the principles of Alternative Dispute Resolution (ADR) and restorative justice, as it emphasizes peace, participation, and the restoration of social relationships. Legally, the existence of customary dispute resolution is grounded in Article 18B(2) of the 1945 Constitution, Article 3 of the Land Law (UUPA), and Law No. 6 of 2014 on Villages. Although effective in maintaining social harmony, customary dispute resolution still faces challenges, including a lack of written evidence and weak legal certainty. Therefore, strengthening is needed through the documentation of customary practices, the drafting of minutes of agreements, and coordination with land offices so that the resolution of customary land disputes has legal certainty without disregarding the social values of indigenous communities.